The concept, Essence, and Meaning of the Principle of “Adaptation (Adjustment) of Working Conditions - Prylypko, Sergii; Pohorielova, Oleksandra; Прилипко, Сергій Миколайович; Прилипко, Сергій (Public organization „LEX PRO OMNES”, 2022)
This paper aims to provide a thorough theoretical and legal overview of the feasibility of introducing a new sectoral principle of labor law, “adaptation (adjustment) of working conditions”, to justify an understanding of “adaptation (adjustment) of working conditions”, and to provide the social value of the principle of adaptation (adjustment) of working conditions in labor law. The article substantiates the need to expand the system of sectoral principles of labor law by means of the principle of “adaptation (adjustment) of working conditions”, a legal idea generated by changes in the environment caused by the coronavirus pandemic and other factors. Its aim is to understand the principle of adaptation (adjustment) of working conditions as a process and/or result of the temporary regular adjustment changes in working conditions in accordance with the requirements of the objective circumstances of the external or production environment, resulting in turn in the creation of a new temporary legal regime of organization of employee working conditions. The generality of this principle in labor law enables the revision of any working conditions for all categories of workers when dangerous factors or circumstances threaten their life or health without prejudice to the permanence of labor legal relations. The social value of the principle of adaptation (adjustment) of working conditions is defined by the author through its ability to provide self-adjustment, natural restructuring, change, and transformation of working conditions in relation to the needs caused by external and internal objective factors in the external or production environment by the value orientation of the rights, freedoms, and interests of workers to protect and defend their life and health as one of the highest social values.
Keywords: adaptation; adjustment; life and health of a worker; objective circumstances; labor conditions